Co-design of a walking activity intervention for stroke survivors - Wittink, H.; van Gessel, C.; Outermans, J.; Blatter, T.; Punt, M.; van der Lugt, R. (Frontiers in Rehabilitation Sciences, 2024)
Introduction: Stroke survivors may not There is a lack of effective interventions to maintain gains made in gait performance after Task Oriented Circuit training for stroke survivors. Behavior change interventions may enhance long term adoption of physical activity. This study used Participatory design methods, such as co-design method, might be helpful into developing an interventions and tools that facilitate physio-and exercise therapists in supporting an active lifestyle, defined as a lifestyle that integrates daily walking activityperformance, in stroke survivors.Objective: 1. to describe the insights generated during the co-design process and 2. to describe the tools that were developed during the co-design process.Methods. A multidisciplinary team consisting of staff members of the Royal Dutch Society for Physical Therapy, kinetic exerciseand physiotherapists, specialized in neuro rehabilitation and conducting Task Oriented Circuit Class training in primary care settings or day therapy centers within residential care facilities, stroke survivors and their carers, experts on measuring movement behavior in stroke survivors, a company specialized in manufacturing sensors and related software, behavioral change specialists, and co-designers collaborated together in a three stage (define, develop and deliver) co-design process.Results: In the design process, the team iteratively developed a prototype accelerometer system for measuring walking behavior performance with a feedback function for stroke survivors and their therapists and a prototype toolbox for therapists to support facilitating behavioral change in their stroke survivors.Discussion: This study shows how co-design can be applied to develop interventions for stroke survivors. The prototype system for measuring walking behaviorperformance and the toolbox both incorporate behavioral change techniques to support a more physically active lifestyle in stroke survivors. Further research will investigate the feasibility of the intervention.